1989
DOI: 10.1093/ptj/69.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Auricular Transcutaneous Electrical Nerve Stimulation on Distal Extremity Pain: A Pilot Study

Abstract: The purpose of this pilot study was to determine the effectiveness of auricular acupuncture-like transcutaneous electrical nerve stimulation on pain. Fifteen subjects (6 men, 9 women) experiencing distal extremity pain received either one placebo pill or a 10-minute treatment of acupuncture-like TENS bilaterally to five acupuncture points on the auricle. Pain levels were measured before treatment and at 0, 10, and 30 minutes posttreatment using the visual analogue scale (VAS) and the pain rating index (PRI) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Twelve trials did not specify whether bilateral or unilateral acupoints were used. Most of the trials reported positive outcomes; however, one trial showed AA was less effective when compared to local analgesic use [27]; two trials reported mixed results (multiple times points of pain scores) [13, 23]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve trials did not specify whether bilateral or unilateral acupoints were used. Most of the trials reported positive outcomes; however, one trial showed AA was less effective when compared to local analgesic use [27]; two trials reported mixed results (multiple times points of pain scores) [13, 23]. …”
Section: Resultsmentioning
confidence: 99%
“…Among these 13 trials, two studies [20, 43] used a 0–100 scale to measure pain, while the eleven other studies used a 0–10 scale. Seven studies reported statistically significant pain relief of auricular therapy compared to the sham group [20, 21, 32, 34, 36, 39, 41, 43], while six studies found no significant difference in pain relief between auricular therapy and the sham control [24, 26, 27, 29, 31, 32]. Among the 13 trials, auricular therapy was found to be a significant method of pain relief when compared to the sham or control group (SMD = − 1.59,  95%  CI  [−2.36, − 0.82], P = 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeh et al in 2014 performed review 15 of ear acupuncture for immediate pain relief (15 minutes) in non-ED conditions and documented 2 acupuncture versus sham studies involving the changing of burns dressings 42 and chronic distal extremity pain. 43 Both studies showed significant but small effect-size differences favoring ear acupuncture (SMD = 0.37 and 0.34, respectively). 15 The current authors' prior meta-analysis of acupuncture versus sham included both body (6 RCTs) and ear (2 RCTs) acupuncture, and the results also favored acupuncture for a broader range of conditions, with a large effect-size and improved patient satisfaction.…”
Section: Effectiveness Across Study Groupsmentioning
confidence: 94%
“…The range of conditions studied included chronic neck, 33 low back, 32 cancer, 14 temporomandibular joint, 43 and distal extremity pain. 44 Of the five studies, two were rated good, one was rated fair, and two were rated poor ( Table 1). The overall change in pain score shows significant improvement for acupuncture treatment versus control (SMD 1.84; 95% CI: 0.60, 3.07; five studies).…”
Section: Chronic Painmentioning
confidence: 99%